Entrenched informality: How non-enforcement, fintech, and digital payments are challenging development in Latin America - Matías Dewey (economic sociology. perspectives and conversations, 2024)
In the late 1990s, José emigrated from Bolivia to Buenos Aires, Argentina. There, he found a formal job, which he lost in 2000. The following year, in 2001, José obtained 50 dollars and, using his mother's sewing machine, began informally manufacturing children's caps and selling them in La Salada, an informal garment-oriented marketplace located in a disadvantaged suburb of the Buenos Aires metropolitan area. Twenty-three years later, José is still producing and trading in this economy. He now has two production facilities, manufactures an average of 10,000 caps per month, and informally employs 16 people.
Keywords: 300